Constraints faced by Cotton Growers in Bt. Cotton Cultivation - M.K. Trivedi,; N.B. Chauhan,; Umesh Chinchmalatpure, (Journal of Agricultural Extension Management, 2025)
Bt. Cotton is the most extensively studied cotton variety today. Scientific studies conducted in India and abroad demonstrate that St.Cotton and its products are safe for the environment, humans, animals and agriculture. "Bt" is the short form of Bacillus thuringiensis, a naturally occurring gram-positive soi l bacterium. During 2005, India had the largest proportional increase in area under St.Cotton from 5 lakh hectares during 2004 to 13 lakh hectares in 2005. This has brought down the sale of non- Bt-Cotton seeds from 15 lakh packets last year to five lakh packets (Anonymous, 2006)